Moral expertise revisited - Gordon, John-Stewart (Bioethics, 2023)
In recent years, there has been a lively (bio-)ethical debate on the nature of moral expertise and the concept of moral experts. However, there is currently no common ground concerning most issues. Against this background, this paper has two main goals. First, in more general terms, it examines some of the problems concerning moral expertise and experts, with a special focus on moral advice and testimony. Second, it applies the results in the context of medical ethics, especially in the clinical setting. By situating the debate in the clinical setting, one arrives at some important conclusions to better understand the relevant concepts and vital problems in the general discussion on moral expertise and the requirements of who counts as a moral expert.